Policies of Regional State Officials in Managing Non-Natural Disasters Covid 19 Based on Indonesian Regulations Relating to Criminal Acts of Corruption - Lihawa, Lesly Deiby; Mawuntu, Ronald; Senewe, Emma; Pinasang, Ralfie (Journal of The Community Development in Asia, 2024)
The Indonesian government has the goal of protecting the entire Indonesian nation during the Covid-19. Regional governments, especially state officials in the regions, make policies to save people in the regions by using existing budgets within the regional government. In Law Number 2 of 2020, the policy is that the regional government allocates funds for dealing with Covid-19. The regional government’s policy, which is essentially to save society in the midst of the Covid-19 pandemic, is not in line with society’s expectations. The public considers that the policies issued by the Regional Government are not on target, so many people think that these policies are projects from the government that take advantage of the non-natural disaster COVID-19. State officials in the regions sometimes interpret discretion in government affairs, especially in handling. The non-natural disaster COVID-19 has implications for abuse of authority and arbitrariness, as well as exceeding authority in carrying out government duties. Problems that occur in the regions relate to policy aspects used by state officials in the regions in handling the non-natural disaster Covid-19 which gives rise to criminal acts of corruption.